2004
DOI: 10.1093/ps/83.9.1518
|View full text |Cite
|
Sign up to set email alerts
|

Ornithine decarboxylase: haplotype structure and trait associations in White Leghorn chickens

Abstract: Sequence analysis of 4,230 bp of the 3' end of the ornithine decarboxylase gene of 20 chickens from a noninbred White Leghorn strain revealed a total of 62 polymorphisms. Of these 61% were transitions, 24% were transversions, and 16% were deletions or insertions. Despite the high number of polymorphisms, only 3 haplotypes were present among the 40 alleles analyzed. Based on the genetic distances between haplotypes they segregated early during domestication of the chicken. Ornithine decarboxylase is a pivotal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…On chromosome 2, a feed-intake QTL was reported by van Kaam et al (1999). The distal part of chromosome 3 was reported to carry a QTL for RFI (De Koning et al, 2004;Parsanejad et al, 2004). Both regions on chromosome 4 were previously reported as carrying feed-intake QTL, at 37 Mb by van Kaam et al (1999) and at 78 Mb by Tuiskula-Haavisto et al (2002).…”
Section: Localization Of Genomic Regions Associated With Feed Intake mentioning
confidence: 84%
“…On chromosome 2, a feed-intake QTL was reported by van Kaam et al (1999). The distal part of chromosome 3 was reported to carry a QTL for RFI (De Koning et al, 2004;Parsanejad et al, 2004). Both regions on chromosome 4 were previously reported as carrying feed-intake QTL, at 37 Mb by van Kaam et al (1999) and at 78 Mb by Tuiskula-Haavisto et al (2002).…”
Section: Localization Of Genomic Regions Associated With Feed Intake mentioning
confidence: 84%
“…De plus, le gène codant pour le récepteur à la FSH a été retrouvé associé avec la ponte (EN) et le poids d'oeuf (EW) . Le gène ODC1 a été montré comme étant associé à la ponte (AFE) et à la solidité de la coquille (SGRAV) (Parsanejad et al 2004). ODC1 est une enzyme régulant la division cellulaire, la différenciation cellulaire et l'apoptose.…”
Section: / Discussionunclassified
“…Except for the region from 50 to 80 Mb on Gga1 and from 30 to 40 Mb on GgaZ, the associations were population/ study specific. Numerous candidate genes have been identified that show significant association between variants and age at first egg: RALGAPA1 (Ral GTPase-activating protein, alpha subunit 1 (catalytic)) and GTPase-activating Rap/RanGAP domain-like 1 gene (Shen et al, 2012); GNRH1 (gonadotropinreleasing hormone 1 (luteinizing-releasing hormone)) DRD2 (dopamine receptor D2; Xu et al, 2011); ODC1 (ornithine decarboxylase 1; Parsanejad et al, 2004); nuclear receptor coactivator 1 gene (Huang et al, 2011); myostatin gene (Zhang et al, 2012); GDF9 (growth differentiation factor 9; Huang et al, 2015); and STAT5B (signal transducer and activator of transcription 5B; Ou et al, 2009). Most of these genes belong to the hypothalamic-pituitary-gonad axis pathway or influence growth and development.…”
Section: Age At First Eggmentioning
confidence: 99%